2008
DOI: 10.1128/aem.00070-08
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Methanogenic Archaeal Community during Plant Residue Decomposition in an Anoxic Rice Field Soil

Abstract: Incorporation of plant residues strongly enhances the methane production and emission from flooded rice fields. Temperature and residue type are important factors that regulate residue decomposition and CH 4 production. However, the response of the methanogenic archaeal community to these factors in rice field soil is not well understood. In the present experiment, the structure of the archaeal community was determined during the decomposition of rice root and straw residues in anoxic rice field soil incubated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
178
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(203 citation statements)
references
References 45 publications
(65 reference statements)
21
178
2
2
Order By: Relevance
“…As reported in previous studies (Peng et al 2008;Lu et al 2015), our study showed that straw addition increased CH 4 production. The addition of nitrate with straw reduced CH 4 production compared with the treatment with straw alone.…”
Section: Discussion Physicochemical Parameterssupporting
confidence: 89%
See 4 more Smart Citations
“…As reported in previous studies (Peng et al 2008;Lu et al 2015), our study showed that straw addition increased CH 4 production. The addition of nitrate with straw reduced CH 4 production compared with the treatment with straw alone.…”
Section: Discussion Physicochemical Parameterssupporting
confidence: 89%
“…A clear shift from Methanosarcinaceae to Methanosaetaceae was observed on day 5 in treatments with nitrate by analysis of transcripts. An expected change of acetate concentrations was observed in these treatments, with accumulation in the early stages of incubation with a subsequent decrease; this was strongly in accordance with earlier reports (Jetten et al 1992;Peng et al 2008). Moreover, higher levels of nitrate (NO 3 − ), nitrous oxide (N 2 O), and sulfate (SO 4 2− ) in the same p e r i o d i n t h e s e t r e a t m e n t s p r o b a b l y a f f e c t e d Methanosarcinaceae and Methanosaetaceae.…”
Section: Responses Of the Methanogenic Communities To Treatmentssupporting
confidence: 93%
See 3 more Smart Citations